Structural assessment of glass used in façade industry. (October 2021) - Naqash, Muhammad Tayyab; Formisano, Antonio; Noroozinejad Farsangi, Ehsan
Abstract: Glass is an integral part of the facades industry. It is not easy to conceive contemporary architecture without using glass material. However, due to complex architectural design, façade structural engineers face difficulty simplifying the development of structural models. Hence, in this paper, initial synopsis is made to verify strength and deflection using structural codes for glass. It is also summarized frequently used standards referred to in further testing of curtain walls. Additional tools usually developed by the manufacturer are required to design anchor bolts; hence suggestions are provided for the technicians related to connections and anchors used in the façade systems. These tools are pretty handy for anchors' design for the base plates or shoe brackets in cracked or uncracked concrete. In the design phase, the manufacturer catalog is a quick source to cross-check the numerical solution, usually referred to in a complete numerical model. Because of this, assessments of real cases using glass as a structural material are presented with the help of numerical codes to find the glass integrity, strength, and serviceability following the acceptance and specified values.